Study on the Optimization of Aeration Scheme for a Spillway - SHI Die; LI Guodong; HE Cuiling; LI Pengfeng (Renmin Zhujiang)
Cavitation damage is easy to occur in discharge structures with high head and large flow.Based on the spillway project of a hydropower station in Northwest China,this paper studies the aeration and cavitation mitigation of spillway through the single hydraulic model test.The experimental results show that:The velocity of spillway chute is larger and the flow cavitation number is less than 0.3 under different conditions of flood frequency,so it is necessary to set up aeration and cavitation mitigation facility.Through the analysis of the cavitation mitigation effect of three different aerators,it can be seen that the aerator with flip bucket can mitigate cavitation,but there are different degrees of splash in the downstream.The aerator with convex bucket can form a stable cavity,and there is no splash in the downstream.The aerator with chute can form a stable cavity and flow pattern in the chute,and it is easy to construct,so it is the optimal aerator.In the optimal aerator,the aeration concentration from aerator to the front of the bucket lip is higher,which is 0.9%~63.1%,the aeration effect is good,and the purpose of aeration and cavitation mitigation is achieved.The research results can provide theoretical guidance and technical support for the follow-up energy dissipation and erosion control research of this project and the aeration and cavitation mitigation research of similar projects.